History of the Jews in Quebec - Anctil, Pierre (Canadian studies (Ottawa, Ontario), 2021)
Over the four centuries discussed, the Jews of Quebec realized that they belonged to a unique society in North America. Their commitment to defend their rights and their extensive contributions to numerous sectors of activity have fostered the development of a Quebec enhanced by diverse identities. Quebec Judaism in its Montreal incarnation took a long time and successive waves of migration from various regions to take root. This work recounts these different contributions throughout the years and the cultural context that encouraged the emergence in Montreal of a Judaism like no other in North America. This is the first overview of a historical narrative that began during the French Regime and continued, through many twists and turns, until the turn of the twenty-first century. The fruit of over thirty years of research conducted in several seldom consulted archives, it paints a complete picture of the highly unique journey Jews undertook in Quebec, a journey that is still largely unknown today.